MUSLIM CONSUMER BEHAVIOR IN THE SHARIA MAQOSID PERSPECTIVE - Soritua Ahmad Ramdani Harahap; Muhammad Ulul Azmi; Achmad Arif (Universitas Darussalam Gontor, 2020)
This study discusses explaining about Muslim consumers in using maqoshid based on sharia. In this study using a type of qualitative research using the literature study method. The results of this study indicate that the benefits obtained from buying goods and services obtained with sincere intentions for worship will produce the goal of mashlahah that can be realized with halal activities. Islam has allowed its people to produce lawful things to produce something useful. In the view of Islam, Muslims must buy goods and services with a principled principle that is approved by Tayyiban in verse Al-Baqarah verse 168 and one of them is to ask our permission (hifdz nafs).